Understanding User Behavior Through Log Data and Analysis - Dumais, Susan; Jeffries, Robin; Russell, Daniel M.; Tang, Diane; Teevan, Jaime (Ways of Knowing in HCI, 2014)
HCI researchers are increasingly collecting rich behavioral traces of user interactions with online systems in situ at a scale not previously possible. These logs can be used to characterize user interactions with existing systems and compare different designs. Large-scale log studies give rise to new challenges in experimental design, data collection and interpretation, and ethics. The chapter discusses how to address these challenges using search engine logs, but the methods are applicable to other types of log data.